Post-weaning weight gain and pregnancy rate of beef heifers bred at 18 months of age: a meta-analysis approach - Canellas,Leonardo Canali (2012)
The objective of this study was to evaluate, using meta-analysis, the main factors related to post-weaning body weight and weight gain that affect pregnancy rate of heifers bred at 18 months of age. Data of 1398 beef heifers from six experiments were analyzed as a set. Information related to methodology and results of each experiment were codified in Microsoft Excel spreadsheets. The independent variables analyzed were: body weight at seven months of age (BW7M), daily weight gain from seven to 12 months (DWG7-12), body weight at 12 months of age (BW12M), daily weight gain from 12 to 15 months (DWG12-15), body weight at 15 months of age (BW15M), daily weight gain from 15 to 18 months (DWG15-18), daily weight gain from 7 to 18 months (DWG7-18) and body weight at 18 months of age (BW18M). The response variable was pregnancy rate (PR). Body weight at 18 months of age and DWG7-18 showed high correlation with PR and between each other. The other variables presented low correlation with PR. Body weight at first breeding and daily weight gain from seven to 18 months are the most important variables affecting the pregnancy rate of heifers bred at 18 months of age in the autumn. Weaning weight and weight gain during intermediate steps of the post-weaning period are not good predictors of pregnancy rate. Higher pregnancy rates can be obtained provided enough post-weaning weight gain and minimum body weight at first breeding are achieved, irrespective of when weight is gained.